Clinical characteristics of children infected with SARS-CoV-2 in Italy - Isabella Tarissi De Jacobis; Rosa Vona; Camilla Cittadini; Alessandra Marchesi; Laura Cursi; Lucrezia Gambardella; Alberto Villani; Elisabetta Straface (BMC, 2021)
Abstract Background Since December 2019 coronavirus disease (COVID-19) emerged in Wuhan and spread rapidly worldwide. Despite the high number of people affected, data on clinical features and prognostic factors in children and adolescents are limited. We propose a retrospective study aimed to evaluate clinical characteristics of children infected with SARS-CoV-2 in Italy. Methods A pediatric population admitted with COVID-19 to Bambino Gesù Children's Hospital of Rome (Italy) in the period from the end of February to July 2020 has been studied. Medical history, comorbidities, symptoms and laboratory findings were obtained from patients' electronic medical records. Results In 66 patients (35 males and 31 females) we found that: i) fever and cough were the dominant symptoms, while vomit and convulsions were rare symptoms; and ii) all ages of childhood were susceptible to COVID-19. Furthermore, we found that, compared to females, males with COVID-19, although not significantly, had higher values of inflammatory markers such as C-reactive protein (CRP) and ESR. Conversely, we found that COVID-19 positive females were older than males and required more days of hospitalization. Both males and females COVID-19 positives had procalcitonin values within the normal range and D-Dimer values slightly higher than the normal range. With regard to this latter marker, the value measured in females, although not significant, was higher than that measured in males. Interestingly, the presence of leukopenia was found in both sexes. Conclusions Compared to the adults we found that COVID-19 infection in children is a non-severe inflammatory disease in both males and females. In any case, many detailed studies should be conducted.